Long-Acting Reversible Contraceptive Placement Among Active-Duty U.S. Army Servicewomen. Issue 5 (May 2017) - Erickson, Anne K.; Nelson, D. Alan; Shaw, Jonathan G.; Loftus, Pooja D.; Kurina, Lianne M.; Shaw, Kate A.
Abstract : OBJECTIVE: To quantify uptake of long-acting reversible contraceptives (LARC)—intrauterine devices (IUDs) and hormonal implants—among U.S. Army active-duty female soldiers and identify characteristics associated with uptake. METHODS: This retrospective cohort study used the Stanford Military Data Repository, which includes all digitally recorded health encounters for active-duty U.S. Army soldiers from 2011 to 2014. We analyzed data from women aged 18–44 years to assess rates of LARC initiation using medical billing codes. We then evaluated predictors of LARC initiation using multivariable regression. RESULTS: Among 114, 661 servicewomen, 14.5% received a LARC method; among those, 60% received an IUD. Intrauterine device insertions decreased over the study period (38.7–35.9 insertions per 1, 000 women per year, β=0.14, 95% confidence interval [CI] –0.23 to –0.05, P <.05), whereas LARC uptake increased, driven by an increase in implant insertions (20.3–35.4/1, 000 women per year, β=0.41, CI 0.33–0.48, P <.001). Younger age was a positive predictor of LARC uptake: 32.4% of IUD users and 62.6% of implant users were in the youngest age category (18–22 years) compared with 9.6% and 2.0% in the oldest (36–44 years). The likelihood of uptake among the youngest women (compared with oldest) was most marked for implants (adjusted relative risk 7.12, CI 5.92–8.55; P <.001). A total of 26.2% of IUD users had one child compared with 13.2% among non-LARC users (adjusted relative risk 1.94, CI 1.85–2.04, P <.001). The majority (52.2%) of those initiating IUDs were married, which was predictive of uptake over never-married women (adjusted relative risk 1.52, CI 1.44–1.59, P <.001). CONCLUSION: Among servicewomen, we observed low but rising rates of LARC insertion, driven by increasing implant use. Unmarried and childless soldiers were less likely to initiate LARC. These findings are consistent with potential underutilization and a need for education about LARC safety and reversibility in a population facing unique consequences for unintended pregnancies. Abstract : Among U.S. soldiers, long-acting reversible contraception use remains low but is slowly rising as a result of increased uptake of implants.